The YMCA in Central European Countries as One of the Ways of Americanising Central Europe after the First World War (Base of Information and Methodological Approaches zo Researching the Issue) - Tomáš Tlustý (Karolinum Press, 2014)
The YMCA in Central European Countries as One of the Ways of Americanising Central Europe after the First World War (Base of Information and Methodological Approaches zo Researching the Issue) The YMCA is essentially an organisation uniting people of Christian faith. The basis of its work was the so-called "Four-way program", which included religious (spiritual), educational and physical education activities. This organisation was established in London in 1844, having been formed by sales clerk George Williams. The YMCA began to spread rapidly throughout Great Britain. From here it spread to France and subsequently to Holland and Germany. It particularly flourished in the United States of America and came to Czechoslovakia from there after the First World War. Here, the YMCA began to establish military and later student residences. It played an important role in developing basketball, volleyball and other sports. It significantly contributed to the rise of permanent summer camps. It also brought a new view of the world, emerging from American Protestantism. The basic method we have decided to use is the comparative method. Using this classic method of historical research, it is necessary to compare the extent to which the YMCA organisation contributed to the "Americanisation" of national cultures of observed countries and how much it influenced young people. Due to the anticipated inequality and imbalance of sources, the method of probing will have to be used to assess individual regions. Unpublished archive materials as well as magazines and news reports from the period, which have not been systematically researched as yet, will be used as sources of information. YMCA ve středoevropských zemích jako jedna z cest amerikanizace střední Evropy po 1. světové válce (informační báze a metodologické přístupy k řešení problému) YMCA je v první řadě organizace sdružující lidi křesťanského vyznání. Základem její práce byl takzvaný "Čtyřstranný program", do kterého patřila činnost náboženská (duchovní), vzdělávací a tělovýchovná. Tato organizace vznikla v roce 1844 v Londýně, kde ji založil obchodní příručí George Williams. Organizace se začala rychle šířit po Velké Británii. Odtud se rozšířila do Francie, následně do Holandska a Německa. K jejímu velkému rozkvětu došlo především ve Spojených státech amerických, odkud se dostala po 1. světové válce do Československa. YMCA zde začala zřizovat vojenské a později studentské domovy. Zasloužila se o rozvoj basketbalu, volejbalu a dalších sportů. Výrazně zde přispěla ke vzniku trvalých letních táborů. Rovněž přinesla nový názor na svět vycházející z amerického protestantismu. Základní metoda, kterou budeme užívat, je metoda komparativní. Pomocí této klasické metody historického výzkumu je nutno porovnat podíl organizace YMCA na "amerikanizaci" národních kultur sledovaných zemích a míru ovlivnění mládeže. Vzhledem k předpokládané nerovnoměrnosti a nevyváženosti pramenů bude nutno využít metodu sondy k posouzení jednotlivých regionů. Při zpracovávání informací bude využíváno nepublikovaných archivních materiálů, dobových časopisů a novinových zpráv, které dosud nebyly systematicky zpracovány.